Origins and frequencies of SLC26A4 (PDS) mutations in east and south Asians: global implications for the epidemiology of deafness. Issue 4 (1st April 2003) - Park, H-J; Shaukat, S; Liu, X-Z; Hahn, S H; Naz, S; Ghosh, M; Kim, H-N; Moon, S-K; Abe, S; Tukamoto, K; Riazuddin, S; Kabra, M; et al.
Abstract : Recessive mutations of SLC26A4 ( PDS ) are a common cause of Pendred syndrome and non-syndromic deafness in western populations. Although south and east Asia contain nearly one half of the global population, the origins and frequencies of SLC26A4 mutations in these regions are unknown. We PCR amplified and sequenced seven exons of SLC26A4 to detect selected mutations in 274 deaf probands from Korea, China, and Mongolia. A total of nine different mutations of SLC26A4 were detected among 15 (5.5%) of the 274 probands. Five mutations were novel and the other four had seldom, if ever, been identified outside east Asia. To identify mutations in south Asians, 212 Pakistani and 106 Indian families with three or more affected offspring of consanguineous matings were analysed for cosegregation of recessive deafness with short tandem repeat markers linked to SLC26A4 . All 21 SLC26A4 exons were PCR amplified and sequenced in families segregating SLC26A4 linked deafness. Eleven mutant alleles of SLC26A4 were identified among 17 (5.4%) of the 318 families, and all 11 alleles were novel. SLC26A4 linked haplotypes on chromosomes with recurrent mutations were consistent with founder effects. Our observation of a diverse allelic series unique to each ethnic group indicates that mutational events at SLC26A4 are common and account for approximately 5% of recessive deafness in south Asians and other populations.